Coconut juice for sporting spirits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Fresh coconut water from young coconuts is said to be a future competitor to the commercially available sports drinks and pasteurised coconut drinks. FAOs Agricultural Industries and Post-harvest Management Services developed a cold sterilisation...